A systematic review and meta-analysis on the prevalence and demographic risk factors of work-related musculoskeletal disorders in construction workers - Santos, Weiner; Lorente, Alejandro; Rojas, Carmen; Isidoro, Rui; Dias, Ana; Mariscal, Gonzalo; Zabady, Ahmed Hamdy; Lorente, Rafael (Frontiers in Public Health, 2025)
IntroductionConstruction workers, who are constantly engaged in physically demanding tasks, face a significant prevalence of work-related musculoskeletal disorders (WMSDs). These conditions affect their quality of life and work performance and call for immediate attention. This study delves into the prevalence of WMSDs among construction workers and the associated demographic risk factors, highlighting the issue’s urgency.MethodsOur research process was thorough. Our search spanned electronic databases like PubMed, Scopus, Cochrane, Embase, and Web of Science. We included studies that involved adult construction workers reporting the prevalence of WMSDs such as back pain, neck pain, and other musculoskeletal diseases. The data were rigorously analyzed using R software, with subgroup and meta-regression analyses to assess the association between demographic factors and the prevalence of WMSDs.ResultsThe prevalence pooled by the meta-analysis was 59% for WMSDs from 14 studies with extensive study-level heterogeneity. Subgroup analysis illustrated differences by region, with higher prevalence in Asia (63%) compared to America (39%) and Africa (52%). Analysis of demographic factors identified the prevalence as significantly higher in the male gender (OR = 19.60). Workers over 40 were likelier to have WMSDs (OR = 39.04). Daily work hours were inconsistently associated. Lower back and shoulders were the most affected body regions.ConclusionOur findings underscore the need for further research to identify other risk factors and design effective prevention strategies. The high incidence of WMSDs among construction workers, significantly related to demographic factors such as gender and age, calls for continuous investigation and the introduction of targeted interventions like work rotation, ergonomic training, and psychosocial support. These measures are crucial in preventing WMSDs and promoting the well-being and performance of construction workers.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/BJ9KV.